Pliny the Elder and Nicholas of Poland on Snake Products and Their Medical Applications - Adriana Grzelak-Krzymianowska (Clotho)
The paper aims to show how Pliny the Elder, in his Historia Naturalis, and Nicholas of Poland, in Experimenta, the medical treatise attributed to him, presented and described ways of preparing snakes for medical purposes. The paper explores the connections and relationships between these texts, primarily in terms of the instructions conveyed regarding the use of specific snake and viper products and the effects of their use on human health, including the many diseases known since antiquity that plagued Nicholas’ contemporaries.